The Impact of U.S. and UN Sanctions on Iraqi Political Elite - R. Sh. Mamedov (MGIMO University Press, 2020)
The problem of sanctions effectiveness as a means of a regime change is one of the key issues for researchers in the field of sanctions policy. The case of U.S. and UN sanctions against Iraq is one of the most vivid examples of how sanctions can be effective in terms of limiting the undesirable international behavior of a country, while failing to instigate a regime change and severely hampering the social and economic conditions for general population. The article discusses the dynamics of restrictive measures against Iraq during Saddam Hussein regime, the problems of regimes adaptation to international sanctions as well as the evolution of U.S. and UN sanctions against the country. For this purpose the authors reviewed the key UN sanctions documents, as well as the evolution of the main aspects of Iraqi political regime with regards to the power distribution between different groups. The research shows that sanctions aimed at regime change failed to fulfill this task. Despite constantly degrading social and economic conditions, the Saddam Hussein regime demonstrated considerable resilience. This can be attributed primarily to the use of contradictions of complex tribal and religious composition of the country, as well as to oppression and a relatively effective re-distribution of the scarce resources between different power groups. Under these conditions, even the presence of intra-elite conflicts strengthened the regime, rather than weaken it. Another important factor was the very policy of external pressure on the elite and the country as a whole. The severity of restrictive measures was partially offset by the presence of programs such as “Oil-for-Food”, which, given the poor development of the programs themselves, as well as corruption schemes involving its executors, reduced pressure on the regime and, consequently, the effectiveness of sanctions. Thus these factors contributed to the ultimate failure of the sanctions policy towards Iraq in 1990-2003.